Clinical-morphological peculiarities of the first trimester of pregnancy on the background of chronical urogenital chlamydiosis - S. Yu. Yuriev; S. A. Krotov; S. S. Antonova; N. N. Goncharova; L. R. Mustafina (Бюллетень сибирской медицины)
Comparison of clinical manifestation of various forms chlamydial infection with a ultrasonic picture and cytomorphological characteristics decidua basalis in the first trimester of pregnancy was carried out. The basic clinical markers were colpitis, endocervicitis and threat of fetus wastage. At percistence the pathogene more significant changes echoscopy pictures were found. Expressed stromal edema and increase of expression of a receptor to IL-2 on a lymphocyte membrane at active chlamydial infection were found during morphological research of the decidual tissue. Stability of a population of the big granular decidual lymphocyte СD56++ at any form of urogenital chlamydiosis was revealed.